Refiguring history : new thoughts on an old discipline - Jenkins, Keith, 1943- (Routledge, 2003)
In this engaging sequel to Rethinking History, Keith Jenkins argues for a re-figuration of historical study. At the core of his survey lies the realization that objective and disinterested histories as well as historical 'truth' are unachievable. The past and questions about the nature of history remain interminably open to new and disobedient approaches. Jenkins reassesses conventional history in a bold fashion. His committed and radical study presents new ways of 'thinking history', a new methodology and philosophy and their impact on historical practice. This volume is.